Efeito do tratamento crônico com Enalapril sobre a concentração de glicose, insulina e lipídios do plasma de ratos submetidos ao estresse neurocitoglicopênico - Paulo Augusto Carvalho Miranda (2006)
Background: Neurocytoglucopenia induced by 2-deoxy-D-glucose (2DG)activates hypothalamic glucoreceptors with a consequent increase insympathetic outflow to liver, pancreas, adrenal medulla and adipose tissue which results in increased hepatic glucose production, insulin inhibition and free fatty acid mobilization from adipose tissue. Evidence has being accumulated to the participation of the renin-angiotensin system (RAS) on metabolic regulation, particularly on glucose and lipids. However, the participation of this system on acute stress is still not well understood. Objectives: The aim of this study is to determine the effects of the chronic treatment with enalapril, an angiotensin converting enzyme (ACE) inhibitor, upon plasma glucose, insulin and lipids levels in response to neurocytoglucopenia induced by 2DG in rats. Methods:Adult male Holtsmman rats were treated daily, o.r, with enalapril (10 mg/kg body wt) for two weeks (ED) or vehicle (CD). The animals had atrial catheters inserted through the jugular vein under ether anesthesia two days before 2DG infusion in order to collect blood samples. On the day of the experiments, the rats had their venous catheters rinsed and connected to polyethylene tubes (PE 50) filled with saline. After one hour of resting in their homecages, blood samples were drawn before and 5, 10, 20, 30 and 60 minutes following 2DG infusion (500 mg/kg body wt). As a control group (ES), rats were treated daily with the same amount of enalapril for the same period and submitted to a saline infusion following the same protocol. Results: The rats treated with enalapril (ED and ES groups) did not show significant differences in all basal values when compared to control animals (CD group). There was however a stronghyperglycemic response to 2DG that was not changed significantly by enalapril treatment (ED and CD, NS). It was shown higher peak stress of plasma insulin concentrations in the group of rats treated with enalapril when compared to controls, suggesting an enhanced glucose stimulated insulin secretion in these groups of rats. Besides plasma triglyceride response to 2DG having showed a significant stress increase only in the ED group (ED and CD, p<0,05), the CD and ES groups showed a drop on plasma triglyceride levels that reached significant decrease at 10 and 30 min, respectively (p<0,05). On the other hand, plasma cholesterol levels did not change during the experiments. Conclusions: These data show that chronic enalapril treatment changes the pattern of insulin and triglycerides response to neuroglucopenia without modifying thehyperglycemic response to 2DG, pointing to an alteration determined by RAS blockade upon glucose-induced insulin secretion and the storage oftriglycerides content during a neuroglucopenic challenge.